Postinfectious complications in the posterior pole of the eye in children - Lorenc, Mateusz; Woś, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
The diagnosis of visual disorders in children is often a challenge for ophthalmologists because of difficult cooperation with pediatric patients. That is why a thorough examination and an attempt to find the cause of pathologies in children are particularly important. The aim of this study is to describe rare complications in the posterior pole of the eye in children following upper respiratory tract infections. In a retrospective review, we describe bilateral maculopathy and optic nerve neuropathy in a 16-year-old boy and neovascular membrane formation in a 7-year-old boy based on our own experience. Both cases were preceded by an upper respiratory tract infection. These examples show that less common possible causes of visual disturbances in children should not be ignored and should be taken into account in the differential diagnosis.